IMPLEMENTASI KETENTUAN RESTRUKTURISASI KREDIT TERHADAP DEBITUR WANPRESTASI PADA KREDIT PERBANKAN - Putu Eka Trisna Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The high percentage of non-performance loan (NPL) may bring adverse impact to creditor (banks), the banking sector in general, and also to the economic and financial of the country. To overcome these conditions, Bank of Indonesia issued a policy regarding restructuring. Restructuring is an effort undertaken in the activities of credit to borrowers who have difficulty to meet its obligations. Banks engaged in lending has a restructuring program has been set on the credit policy of each bank, but still there are banks that ignore and do not do this loan restructuring seek in accordance with the procedure. This study is an empirical study that examines the juridical on the implementation of the rules concerning the restructuring of the debtor defaults on bank loans as well as obstacles in implementing the debt restructuring. This research is a descriptive research. Data sourced from primary data and secondary data. Data collection techniques used is literature study and interview techniques. Analysis conducted qualitative and descriptive analysis presented. Implementation of the provisions of the rescue loan restructuring and settlement of non-performing loans on bank credit has not been optimally applied to all borrowers who are having trouble paying even though they have the opportunity to carry out the payment. Inhibiting factors, among others, the rules concerning debt restructuring are scattered in various policy rules, regulations often change with a relatively large number of rules, the lack of a comprehensive understanding of this policy, an independent financial consultant is often overlooked involvement in debt restructuring, which is not good faith to implement agreement, the lack of information and initiatives in the debtor filed debt restructuring, customers who do not cooperative and giving false information about the source of income.